2021
DOI: 10.3389/fnsys.2021.617388
|View full text |Cite
|
Sign up to set email alerts
|

Beta2 Oscillations in Hippocampal-Cortical Circuits During Novelty Detection

Abstract: Novelty detection is a core feature of behavioral adaptation and involves cascades of neuronal responses—from initial evaluation of the stimulus to the encoding of new representations—resulting in the behavioral ability to respond to unexpected inputs. In the past decade, a new important novelty detection feature, beta2 (~20–30 Hz) oscillations, has been described in the hippocampus (HC). However, the interactions between beta2 and the hippocampal network are unknown, as well as the role—or even the presence—o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…memory-guided search (Leonard et al, 2015; Montefusco-Siegmund et al, 2017), and retrieval (Montefusco-Siegmund et al, 2017) or subsequent memory effects (Jutras et al, 2009) in monkeys, or spatial coding and memory in rodents. In addition, a band-limited 20-40 Hz oscillation is seen in rodent CA1 (and is synchronized with LEC (Igarashi et al, 2014)) during discrete item cueing or retrieval such as in olfactory associative place and sequence learning (Allen et al, 2016; França et al, 2014; Lansink et al, 2016; Lopes-Dos-Santos et al, 2018), and when exploring novel environments (França et al, 2021; Trimper et al, 2017). This frequency band is associated with activation of the trisynaptic pathway (DG and CA3, (Colgin, 2016; Fernández-Ruiz et al, 2021; Hsiao et al, 2016; Rangel et al, 2015)), but is also seen in coherent oscillations between CA1 and LEC (Igarashi et al, 2014) implicating direct, temporoammonic pathways, thus the origin of the observed gamma oscillations in primates will be an important topic for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…memory-guided search (Leonard et al, 2015; Montefusco-Siegmund et al, 2017), and retrieval (Montefusco-Siegmund et al, 2017) or subsequent memory effects (Jutras et al, 2009) in monkeys, or spatial coding and memory in rodents. In addition, a band-limited 20-40 Hz oscillation is seen in rodent CA1 (and is synchronized with LEC (Igarashi et al, 2014)) during discrete item cueing or retrieval such as in olfactory associative place and sequence learning (Allen et al, 2016; França et al, 2014; Lansink et al, 2016; Lopes-Dos-Santos et al, 2018), and when exploring novel environments (França et al, 2021; Trimper et al, 2017). This frequency band is associated with activation of the trisynaptic pathway (DG and CA3, (Colgin, 2016; Fernández-Ruiz et al, 2021; Hsiao et al, 2016; Rangel et al, 2015)), but is also seen in coherent oscillations between CA1 and LEC (Igarashi et al, 2014) implicating direct, temporoammonic pathways, thus the origin of the observed gamma oscillations in primates will be an important topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…during discrete item cueing or retrieval such as in olfactory associative place and sequence learning (Allen et al, 2016;França et al, 2014;Lansink et al, 2016;Lopes-Dos-Santos et al, 2018), and when exploring novel environments (França et al, 2021;Trimper et al, 2017). This frequency band is associated with activation of the trisynaptic pathway (DG and CA3, (Colgin, 2016;Fernández-Ruiz et al, 2021;Hsiao et al, 2016;Rangel et al, 2015)), but is also seen in coherent oscillations between CA1 and LEC (Igarashi et al, 2014) implicating direct, temporoammonic pathways, thus the origin of the observed gamma oscillations in primates will be an important topic for future research.…”
Section: Decoupled Gammamentioning
confidence: 94%
“…Secondly, we investigated potential phase-locking of neuronal spiking to a specific phase of the beta oscillation, which would support the idea that beta oscillations in the retrosplenial cortex are generated locally and not merely volume conducted from another region of the brain (França et al, 2021). For each recording session, histograms showing the probability of neuronal spiking at different phases of the beta oscillation were generated, and Rayleigh's test was performed on these individual phase histograms to investigate potential non-uniformity of these distributions.…”
Section: Multi-unit Activitymentioning
confidence: 82%
“…Since the beta and low-gamma oscillations were suggested to be modulated in the order of minutes during exposure to a novel environment and during exploratory behavior [ 10 , 28 ], we then visualized the change of power spectrum over 20 min of exposure. It can be seen that time-frequency analyses of an example (one animal; Figure 3 A) and group average (six animals in each group; Figure 3 B) both show the gradual change for beta and low-gamma power in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Hippocampal neuronal oscillations in local field potentials (LFP) are known to correlate with memory functions [ 8 , 9 ]. The beta (~20–30 Hz) and low-gamma (~30–55 Hz) oscillations in the CA1 region have been suggested to play a pivotal role in spatial novelty and memory encoding of object location [ 10 , 11 , 12 , 13 ]. These oscillations are intensified during spatial novelty for a few minutes compared to familiar environments [ 11 , 14 ], and the beta oscillation power during novelty exposition is correlated with memory performance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%